Implications of endoplasmic reticulum stress and autophagy in aging and cardiovascular diseases - Ma, Chenguang; Liu, Yang; Fu, Zhiling (Frontiers in Pharmacology, 2024)
The average lifespan of humans has been increasing, resulting in a rapidly rising percentage of older individuals and high morbidity of aging-associated diseases, especially cardiovascular diseases (CVDs). Diverse intracellular and extracellular factors that interrupt homeostatic functions in the endoplasmic reticulum (ER) induce ER stress. Cells employ a dynamic signaling pathway of unfolded protein response (UPR) to buffer ER stress. Recent studies have demonstrated that ER stress triggers various cellular processes associated with aging and many agingassociated diseases, including CVDs. Autophagy is a conserved process involving lysosomal degradation and recycling of cytoplasmic components, proteins, organelles, and pathogens that invade the cytoplasm. Autophagy is vital for combating the adverse influence of aging on the heart. The present report summarizes recent studies on the mechanism of ER stress and autophagy and their overlap in aging and on CVD pathogenesis in the context of aging. It also discusses possible therapeutic interventions targeting ER stress and autophagy that might delay aging and prevent or treat CVDs.